Occurrence and distribution of biomarkers in Baiyinhua lignite. (1st July 2020) - Lv, Jing-Hui; Wei, Xian-Yong; Zhang, Yang-Yang; Zong, Zhi-Min
Highlights: Alkylbenzenes, ketones, and alkenes and alkanes have similar biogenic precursors. Alkenes with different carbon number correspond to diverse biogenic precursors. BL is a typical non-marine lignite formed in mild climate. Both chemical and biochemical reactions contribute to the formation of biomarkers. Abstract: Sequential thermal dissolution (STD) of Baiyinhua lignite (BL) in cyclohexane, methanol, and ethanol was performed at 300 °C to characterize the biomarkers (BMs) in BL. To confirm the origin of the BMs, BL pyrolysis was investigated using a Curie-point pyrolyzer. According to the analysis with a gas chromatograph/mass spectrometer, the BMs detected can be classified into n -alkanes, isoprenoid alkanes, n -alkenes, long-chain alkylbenzenes (ABs), polyarenes, n -alkanones, alkyl-substituted cyclopentanones, and alkyl-substituted cyclopent-2-enones. Except n -alkenes, other BMs are enriched into soluble portions from the STD. The absence of n -alkenes in BL indicates that BL was formed in a mild climate during geological times. The occurrence and distribution of BMs reflect the various pathways of BMs during coalification. The distribution of n -alkanes confirms that BL is a typical non-marine coal. Long-chain n -alkenes could inherently exist in BL, while mid-chain ones were mainly produced from the cleavage of side chains on aromatic rings. In most cases, the distribution of ABs is similar to that of n -alkanes in cyclohexane-soluble portion, suggesting a product-precursor relationship between ABs and n -alkanes. The much higher relative proportion of retene than cadalene illustrates that as for high terrestrial plants, pinaceae significantly contributed to the formation of BL. Organic molecules in living organisms undergo a series of physical, chemical and biochemical changes to produce different BMs. Related mechanisms for the formation of BMs during coalification were discussed.